Populasi Tumbuhan Anggota Famili Zingiberaceae di Blok Koleksi Tumbuhan Sumber Agung DS Tahura Wan Abdul Rachman (Population of Plant of the Zingiberaceae Family Members at Sumber Agung DS Plant Collection Block in Tahura Wan Abdul Rachman) - Dewy, Merty Fertyana; ., Indriyanto (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
The Wan Abdul Rachman Great Forest Park (Tahura) is one of the conservation forests in Lampung Province. The plant collection block serves as a place for the collection of native and artificial plants. The Collection Block has the potential as a place to grow members of the Zingiberaceae family. Zingiberaceae is a flowering plant known as ginger plants. This study aims to determine the population of plants belonging to the Zingiberaceae family in the Sumber Agung Plant Collection Block, Wan Abdul Rachman Great Forest Park. The study was conducted in June-July 2021. The method used was the transect method with a sampling intensity of 0.1% or an area of 1,411.8 m2. There are 4 transect, each measuring 5 m wide and 180 m long. Sample plots measuring 5 m x 2 m were made continuous in all transect. The results showed the population of plants belonging to the Zingiberaceae family in the Sumber Agung Plant Collection Block as many as 15 species, namely temulawak (Curcuma xanthorrhiza), laos (Alpinia galanga), fragrant lempuyang (Zingiber aromaticum), ginger (Zingiber officinale), bitter lempuyang /emprit (Zingiber amarican), tepus (Etlingera solaris), lempuyang elephant (Zingiber zerumbet), temu putih (Curcuma zedoaria), white galangal (Alpinia malaccensis), pacing (Costus spesiosus), temu giring (Curcuma heyneana), bangle (Zingiber purpureum), cardamom (Amomum compactum), honje/kecombrang (Etlingera elatior), and wresah (Amomum delbatum). The dominant population of Zingiberaceae plants is Laos with an INP of 75.809 and a density of 666.6 individuals/ha. Keyword: population; Zingiberaceae; collection blocks; great forest park